PENGARUH KOMUNIKASI DAN PENGEMBANGAN KARYAWAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI AMAROOSSA HOTEL INDONESIA - Ririn Lutfiani; Bambang NS (Human Capital Development, 2016)
Purpose- This study aimed to determine the effect of communication and employee development to employee’s productivity. The population used in this study was employee at Amaroossa Hotel Indonesia (Amaroossa Cosmo Jakarta, Amaroossa Royal Bogor, Hotel Amaroossa Bandung, and Amaroossa Grande Bekasi). Design/methology/approach -The sampling simple random technique was used to select the 120 respondents. The multiple regression method by deployed SPSS vesion 20 to analyze the attained data from respondents. Findings- The results of this study indicate that communication directly influence employee productivity. Employee developments directly influence employee productivity. Research Limitations- The limitation of respondents due to limited populations was one of the limitation that need to be enhanced in the next research. Practical implications- The manager should seek the continual practical method to develop competencies of the organization.